Factors that May Lead on the Non-renewal of Certified Organic Product According to Organic Producers in Brazil - Scalco, Andréa Rossi; Oliveira, Sandra Cristina De; Pigatto, Giuliana Santini; Cobre, Juliana (Sociedade Brasileira de Economia e Sociologia Rural, 2017)
Abstract: The regulatory process of the organic sector in Brazil began in 1999 and has gone through several changes, culminating in the Decree-Law of December 2007, which established rules for the production and trading of organic products in Brazil. In such Decree, the certification has become a compulsory requirement for production and trading of such products, whose rules governing their obtaining follow rigorous controls standards. As the certification process of organic products is recent and there is a lack of studies carried on this subject, this study will contribute to fill the existing gap in the international literature, mainly national about this topic, once that aimed to identify factors that influence the possibility of non-renewal of organic production certificate, according to the perception of certified producers in Brazil. Through this effort, this research should contribute to wider adherence and maintenance of the producer in the certified system or, at least, proposals for further works. A total of 200 producers from several Brazilian states participated in this study, and data analysis was performed using descriptive statistics and, later, exploratory factor analysis. The results achieved holds that the determining factors to the non-renewal of the certificate involve variables related to transactions among operators, organization of the supply chain and to the regulations. Furthermore, to overcome the challenges imposed to rural producers, one of the proposals is for greater effective actions from representative industry entities of the sector in aspects that are related to the certification process.

Resumo: O processo de regulamentação do setor de orgânicos no Brasil se iniciou em 1999 e passou por várias mudanças, culminando no Decreto-lei de dezembro de 2007, que estabeleceu regras para produção e comercialização de produtos orgânicos no Brasil. Em tal decreto, a certificação se tornou requisito compulsório para produção e comercialização de tais produtos, cujas regras para sua obtenção seguem padrões rigorosos de controle. Sendo recente o processo de certificação de produtos orgânicos, esta pesquisa vem contribuir à literatura internacional e, principalmente, nacional, sobre este tema, com o objetivo de identificar os fatores que influenciam a possibilidade de não renovação do certificado de produção de orgânicos, segundo a percepção de produtores certificados do Brasil, e assim propor ações que possam contribuir para adesão e manutenção no sistema certificado. Participaram dessa pesquisa 200 produtores de vários estados brasileiros, e a análise dos dados foi realizada por meio de estatística descritiva e, posteriormente, análise fatorial exploratória. Os resultados apontaram que os fatores considerados determinantes para a não renovação do certificado envolvem variáveis relacionadas às transações entre os agentes, à organização da cadeia produtiva e à regulamentação. Para superar os desafios impostos aos produtores rurais, uma das propostas é que haja maior efetividade das ações das entidades de classe representativas do setor no que se refere aos aspectos relacionados ao processo de certificação.
Keywords: certification; organic producers; exploratory factor analysis.; certificação; produtores orgânicos; análise fatorial exploratória.